Panduan Ringkas Pemeliharaan dan Perbaikan Jembatan Kayu - Sutarto, Tommy E.; Kamil, Insan; Tumingan; Barus, Freddy; Widiawati, Dhiana D.; Firsty, Melviana; Ahmad, Raudah; Wulandari, Fitri; Pamungkas, Pulung P.; Nugroho, Septian A.; Nasir, M. (Politeknik Negeri Samarinda, 2025)
Numerous timber bridges in Samboja District, East Kutai Regency, remain outside the scope of maintenance and rehabilitation programs by both the Provincial and Regency Governments. It is essential to encourage local communities to take initiative and independently engage in the maintenance and repair of these bridges. One effective approach involves providing education and practical demonstrations to raise community awareness and equip them with the necessary skills for timber bridge maintenance and repair. The Civil Engineering Department of Samarinda State Polytechnic organized such an initiative at the Margomulyo Village Meeting House, located in one of the villages in Samboja District. Approximately 35 participants, including local residents, village officials, and neighborhood leaders, attended the session. The program combined educational counseling with community service and hands-on demonstrations of timber bridge inspection and maintenance, facilitated by students from the Civil Engineering Department. The participants actively engaged throughout the event, demonstrating enthusiasm and commitment. As a result of this initiative, the local community has been empowered with practical knowledge and skills to independently maintain and repair timber bridges in their area. Through this combination of education, demonstration, and community service, a foundation for sustainable bridge upkeep has been successfully established. Furthermore, the knowledge and skills can be disseminated to other neighborhoods with similar problems.